2020
DOI: 10.1016/j.chembiol.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic Lysine Lactoylation of Glycolytic Enzymes

Abstract: Highlights d Lysine lactoylation occurs via a non-enzymatic acyl transfer from lactoylglutathione d Glycolytic enzymes are heavily modified by lactoylation d Glyoxalase 2 is the critical regulator for lactoylglutathione and lysine lactoylation d Glycolytic output is significantly repressed in glyoxalase 2 knockout cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
184
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(210 citation statements)
references
References 28 publications
9
184
1
1
Order By: Relevance
“…Besides the important functions of lysine ERPs and the growth-halting effects of lysine deprivation discussed above, lysine is also a versatile AA modified by various modifications including methylation, acetylation, phosphorylation, malonylation, O-GlcNAcylation, SUMOylation, ubiquitination and lactoylation, especially those lysine residues in histones [34][35][36]. These post-translational modifications of lysine and its ERPs regulate the structures and functions of enzymes to expand the functional proteome [36], represent the crosstalk between metabolism and epignome [37], and also link cell signaling and metabolic reconfiguration to cell proliferation and differentiation [38]. Thus, all these support that lysine is an important EAA, its ERPs and their modifications play indispensable roles in homeostasis, proliferation, differentiation and diseases including malnutrition and cancer.…”
Section: Glycine Restriction and Supplementmentioning
confidence: 99%
“…Besides the important functions of lysine ERPs and the growth-halting effects of lysine deprivation discussed above, lysine is also a versatile AA modified by various modifications including methylation, acetylation, phosphorylation, malonylation, O-GlcNAcylation, SUMOylation, ubiquitination and lactoylation, especially those lysine residues in histones [34][35][36]. These post-translational modifications of lysine and its ERPs regulate the structures and functions of enzymes to expand the functional proteome [36], represent the crosstalk between metabolism and epignome [37], and also link cell signaling and metabolic reconfiguration to cell proliferation and differentiation [38]. Thus, all these support that lysine is an important EAA, its ERPs and their modifications play indispensable roles in homeostasis, proliferation, differentiation and diseases including malnutrition and cancer.…”
Section: Glycine Restriction and Supplementmentioning
confidence: 99%
“…An additional ramification of the current results may be in the area of cancer biology, where there has been interest in the potential use of GLO-1 inhibitors to target metabolic vulnerabilities of cancer cells. 51,59 The apparent cardiotoxic effects of SBB-GSH-CpE ( Fig. 6) suggest that caution may be required in the use of such drugs to ensure they do not elicit cardiac toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…While such a finding might cast focus on oxidative stress as a phenotypic driver in Alkbh7 -/- , recent discoveries have implicated the GLO-1/GLO-2 system in epigenetic signaling. Specifically, the product of GLO-1, S-lactoylglutathione (SLG), has been shown to mediate the lactylation of lysine residues ( Gaffney et al, 2020 ), including in histones ( Zhang et al, 2019 ), which may represent a link between metabolism and gene regulation. As such, it is possible that SLG levels may be elevated in Alkbh7 -/- , which could drive epigenetic changes that underlie the phenotypes of the knockout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators identified a non-enzymatic acyl transfer of lactate from LGSH to protein Lys residues of glycolytic enzymes. This "LactoylLys" modification of metabolic proteins characterizes a previously unexplored feedback mechanism for regulation of central metabolism [114]. These studies highlight the interplay between endogenously formed electrophilic metabolites and metabolic regulation of the NRF2-KEAP1 signaling in the EpRE/ARE.…”
Section: Lipid Electrophilesmentioning
confidence: 92%